Rapamycin-loaded nanostructured lipid carrier modified with folic acid intended for breast cancer therapy - Rodero, Camila Fernanda [UNESP]; Luiz, Marcela Tavares [UNESP]; Sato, Mariana Rillo [UNESP]; Boni, Fernanda; Fernandes, Guilherme F.S. [UNESP]; dos Santos, Jean Leandro [UNESP]; Martinez-Lopez, Ana Luisa; Irache, Juan M.; Chorilli, Marlus [UNESP] (Elsevier, 2025)
Breast cancer stands as the most common form of malignancy among women globally, and it showcases commendable rates of cure when detected in early-stage and non-metastatic conditions. To overcome drug resistance and side effects observed in conventional chemotherapy, the present study aims to deliver rapamycin (RAP), a mTOR protein inhibitor, into a nanostructured lipid carrier (NLC) functionalized with folic acid for promoting active targeting to breast cancer cells. In the first step, the synthesis of 1,2-distearoyl-sn-glycero-3-phosphatidylethanolamine-N-[amino(polyethylene glycol)-2000] (ammonium salt) with folic acid (DSPE-PEG2000-FA) was successfully performed and characterized by UV spectroscopy, nuclear magnetic resonance, and infrared spectroscopy. Then, the folic acid-modified NLC loaded with RAP (FA-NLC-RAP) and the unmodified formulation (NLC-RAP) was developed and displayed a size of about 100 nm, negative surface charge, and high RAP encapsulation efficiency (94.92 % and 85.72 %, respectively). In vitro studies suggested that FA-NLC-RAP exhibited a higher degree of internalization in cancer cells (MCF-7) than in normal cells (MCF-10A), demonstrating the potential of folic acid as a ligand for promoting active targeting of RAP for breast cancer cells through folate receptors overexpressed in tumor cells FA-NLC-RAP significantly reduced tumor cell viability, similarly to that observed with the RAP solution. The release profile of the formulation was prolonged. Finally, studies in Caenorhabditis elegans evidenced the safety of FA-NLC-RAP characterized by a complete absence of toxicity in this animal model. Therefore, the findings imply that FA-NLC-RAP holds considerable promise for the treatment of breast cancer.
Keywords: Breast cancer; Folic acid; Nanoparticles; Nanostructured lipid carrier